Applied Social Research in the Healthcare System: New Forms and Meanings of Interdisciplinarity - I. V. Bogdan (Здоровье мегаполиса, 2024)
This article provides a summary of the V Anniversary Forum with International Participation “Sociology of Health: New Forms of Interdisciplinary Synergy,” which took place at the end of 2023. Based on the materials of the Forum, topical issues in the field of applying social research methodologies to healthcare organization are observed. Among them are such topics as the value and strategies for applying interdisciplinary approaches, the emergence of new trends and understanding of old ones in healthcare digitalization (neural networks, new research methods, gamification, transformation of communication), focusing on certain vulnerable population groups, e.g., the senior population and their health, increasing attention to mental health issues, etc. The Forum offered new forms of interdisciplinary dialogue, connecting standard scientific sections with novel ideas such as immersive spaces. According to survey results, the event was highly appreciated by listeners, showing how well it matched their interests.